The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsomega.2c05588
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Simulation of Water Transport through Short Carbon Nanotubes

Abstract: Water transport through short single-walled (6, 6) carbon nanotubes (CNTs) was investigated with ab initio molecular dynamics (AIMD) simulation at different temperatures. The water molecules under extreme confinement present a one-dimensional jagged pattern owing to hydrogen bonding, with the near-perfect alignment of the dipole orientations. CNTs ending with dangling bonds can promote water dissociation near the entrance and the occurrence of dipole flipping along the water wire at high temperatures, accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…9 We further examined the PDH process assisted by neighboring unsaturated edge-Mo atoms within the motif region of the TM 1 -S 4 /edge catalyst, since the dangling bond on the edge-Mo atom normally exhibits high reactivity. [56][57][58] As expected, the energy barrier of a-C dehydrogenation is lowered to 0.76 eV when assisted by the unsaturated edge-Mo atom (TS3 in Fig. 3b).…”
Section: Reaction Mechanism For Pdhsupporting
confidence: 77%
See 2 more Smart Citations
“…9 We further examined the PDH process assisted by neighboring unsaturated edge-Mo atoms within the motif region of the TM 1 -S 4 /edge catalyst, since the dangling bond on the edge-Mo atom normally exhibits high reactivity. [56][57][58] As expected, the energy barrier of a-C dehydrogenation is lowered to 0.76 eV when assisted by the unsaturated edge-Mo atom (TS3 in Fig. 3b).…”
Section: Reaction Mechanism For Pdhsupporting
confidence: 77%
“…5a, the TM 1 -S 4 /edge (TM = Ru, Os) catalysts contain relatively abundant single d electrons among the six candidates, and the resulting unsaturated bonds give the high activities. 57–59,62…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of the dangling bonds might affect the structure and dynamics of confined water molecules as shown by the studies of Corry, Hughes et al and Sahu et al . The AIMD studies of Liu et al demonstrated that the presence of dangling bonds can promote water dissociation near the entrance, however, it was not possible to capture the same in present classical MD simulations. The brief discussion over impact of dangling bonds has been included in Supporting Information as Text S4.…”
Section: Discussionmentioning
confidence: 93%
“…S1 of the ESI, † suggesting enough thermal stability. 41 As evident from Fig. S2 and S3 in the ESI, † the pristine and corresponding perovskite systems are found to be significantly stable in the microcanonical ensemble.…”
mentioning
confidence: 84%